(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article provides information on how the Second World War, one of the bloodiest and most brutal periods in the history of humanity in the 20th century, left a deep mark on the lives of the people of Uzbekistan, including its women. It highlights how, in a country where millions of sons were sent to the front, the heavy economic burden fell on the shoulders of women. They honorably fulfilled crucial tasks, not only preserving the family hearth but also meeting front-line needs and restoring the country’s economy.